Flow of generalized newtonian liquids in screw channel of extruder plasticating system - Steller, R. (Polimery, 2009)
Theoretical analyses of isothermal, stationary and fully developed flows of generalized Newtonian liquids in a screw channel are presented (Fig. 1) in the paper. It is shown that the flow rate can be described by the simple general expression valid for every liquid. Parameters of this expression, which usually should be determined by numerical methods, depend on the type of liquid. Because of this, the effective methods of approximate calculations of these parameters are discussed for the most important practically equation of power law liquid. They lead to the simple equations describing connection of the rate of unidirectional or bidirectional flow and operation parameters of extrusion process (Fig. 2 and 3). Possible applications of the obtained results in the calculations of characteristics of non-isothermal flows in the curved channels of small relative widths and with existence of leakage flows were discussed as well.